Do Estaleiro do Recife à Ribeira das Naus: logística, dinâmicas econômicas e sociais para a construção naval na Capitania de Pernambuco (1755-1788) - Cleverson Fausat (Navigator)
From the second half of the eighteenth century, the Portuguese authorities implemented a series of rules for the extraction and processing of wood from the Captaincy of Pernambuco, with the aim of supplying shipbuilding in Ribeira das Naus in Lisbon. Moreover to the new standards, cataloging expeditions to the corresponding Captaincy of Paraíba, the judicial district of Recife and the District of Alagoas forest portions were enforced. Between 1755 and 1788 six managers of the Captaincy of Pernambuco put into practice the orders issued by the State Department of Navy and Overseas, with the ultimate goal of improving the logistics of the reef site. As a result, we evaluated the best ports for transportation of production, conducted tests on samples of wood at the Royal Army Arsenal and hired new master carpenters from the Kingdom.